ANALYSIS OF THE FORMATION OF VOLUNTEERING ACTIVITIES IN THE SOCIAL SPHERE IN THE WORLD AND IN UKRAINE - Федоров, М.В. (SWorldJournal, 2023)
The article states that the factors that determine the intensification of volunteer activities are the aggravation of social problems in Ukraine. It was emphasized that the key to the creation and construction of a civil society is the development of volu